“Needed but lacked”: Exploring demand- and supply-side determinants of access to cardiopulmonary resuscitation training for the lay public in China - Dong, Xuejie; Kong, So Yeon Joyce; Xu, Hanbing; Ho, Andrew Fu Wah; Blewer, Audrey L.; Birkenes, Tonje Soraas; Myklebust, Helge; Zheng, Xiaojian; Li, Minghua; Zheng, Zhi-Jie; Zhang, Zhifeng; Zhang, Lin (Frontiers in Public Health, 2023)
Background: Despite years of public cardiopulmonary resuscitation (CPR) training efforts, the training rate and survival following out-of-hospital cardiac arrest (OHCA) have increased modestly in China. Access is imperative to increase the public CPR training rate, which is determined by both the demand- (e.g., the lay public) and supply-side (e.g., CPR trainers) factors. We aimed to explore the demand and supply determinants of access to CPR training for the lay public in China. Methods: Qualitative semi-structured interviews were conducted with 77 laypeople (demand-side) and 8 key stakeholders from CPR training institutions (supply-side) in Shanghai, China. The interview guide was informed by the Levesque et.al. healthcare access framework. Data were transcribed, quantified, described, and analyzed through thematic content analysis. Results: On the demand-side, the laypeople’s ability to perceive their need and willingness for CPR training was strong. However, they failed to access CPR training mainly due to lacked information on where to get trained. Overestimation of skills, optimism bias, and misconceptions impeded laypeople from attending training. On the supply-side, trainers were able to meet the needs of the trainees with existing resources, but they relied on participants who actively sought out and registered for training and lacked an understanding of the needs of the public for marketing and encouragement to participate in the training. Conclusion: Insufficient information and lack of initiative on the demand-side, lack of motivation and understanding of public needs on the supply-side all contributed to persistently low CPR training rate in China. Suppliers should integrate resources, take the initiative to increase the CPR training rate, innovate training modes, expand correct publicity, and establish whole-process management of training programs.